The Use of OODEV® in Improving the Reproductive Performance of Male Yellow Rasbora Fish Rasbora lateristriata (Bleeker, 1854) - Hurul Ein; Retnoaji, Bambang; Slamet Widiyanto (Journal of Aquaculture and Fish Health, 2024)
A local commodity, Yellow rasbora fish Rasbora lateristriata (Bleeker, 1854), can potentially be used as a food resource by the Kulon Progo community. Added to that, cultivation or aquaculture is known to optimize this potential. Furthermore, Aquaculture will also prevent illegal fishing in nature, where yellow rasbora fish are listed as vulnerable species in the IUCN Red list. This study induced male yellow rasbora fish using the hormone OODEV® injection, which comprises the hormone Pregnant Mare Serum Gonadotropin (PMSG) and anti-dopamine. PMSG is a hormone that contains FSH as well as LH in it. Yellow rasbora fish were nurtured to the age of six months and treated with four different treatments (dose) for a month, namely 0 mL/Kg, 0.25 mL/Kg, 0.5 mL/Kg, and 0.75 mL/Kg. Observed parameters included motility (movement and duration) as well as sperm count, sperm viability, sperm morphology, sperm morphometry, gonadosomatic index (GSI), and survival rate (SR). Data obtained were analyzed using SPSS with the One-way ANOVA test and continued with Duncan's test if the results were significant. The obtained results had no significant effect on the IGS value (p>0.05), with the highest value found at a dose of 0.75 mL/Kg. In addition, administration of OODEV® also improved sperm quality with the best results at 0.75 mL/Kg  in terms of motility with the highest progressive movement compared to other doses but not significant  (p>0.05) compared to the control,  and significantly (p<0.05) longest movement duration compared to other doses, while in terms of morphometry it had the second widest middle piece area but not significant (p>0.05) compared to other doses, widest tail area but not significant (p>0.05) compared to other doses except with 0.25 mL/Kg, longest tail length  (p>0.05) but not significant with other doses except with 0.25 mL/Kg , and significantly (p<0.05) had the longest sperm total length. Every dose showed a 100% percentage of survival rate.